2021
DOI: 10.1186/s12866-021-02246-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characteristics of drug-resistant Mycobacterium tuberculosis in Hainan, China: from 2014 to 2019

Abstract: Background The emergence of antimicrobial resistance against Mycobacterium tuberculosis (M. tuberculosis) has become the major concern in global tuberculosis control due to its limited therapy options and high mortality. However, the clinical and molecular characteristics of drug-resistant strains vary in different geographical areas. Hainan Island located in southern China, is a high drug-resistant tuberculosis burden area. This study aimed to determine the dynamic changes of drug-resistance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…The clinical and molecular characteristics of the M. tuberculosis strains vary in different areas. This was observed in this study in consonance with the findings of Liu et al [12]. The diversity of mutations can also provide information for investigating the evolutional lineages of M. tuberculosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The clinical and molecular characteristics of the M. tuberculosis strains vary in different areas. This was observed in this study in consonance with the findings of Liu et al [12]. The diversity of mutations can also provide information for investigating the evolutional lineages of M. tuberculosis.…”
Section: Discussionsupporting
confidence: 93%
“…Recent research has revealed that different mutations in M. tuberculosis can confer varying levels of phenotypic resistance to anti-TB medications [6,7,11]. Consequently, the aggregation of mutations at several positions has a comprehensive effect on drug resistance [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we assessed the associated risk factors for rpoB gene mutation in data sourced areas. The rpoB gene mutation rate of retreated TB patients (83.41%) was higher than that of new cases (62.32%), it has been proved that the RIF resistance rate of retreated tuberculosis is higher than that of new cases in previous studies [ 13 , 14 ], the higher rate may since that patients with retreated pulmonary tuberculosis often fail in the initial treatment due to unreasonable or irregular anti-tuberculosis treatment, resulting in the dominant growth of drug-resistant tuberculosis bacteria, and it’s drug resistance mechanism is related to the mutation of rpoB gene which coding RNA polymerase β-subunit [ 3 ]. Notably, we found no rpoB gene mutation in partial RR-TB strains, but mutations in sensitive strains, the inconsistency between gene resistance and phenotype resistance may be caused by heterogeneity of Mtb.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of TB in Hainan Province showed no significant seasonality presented in the spatial–temporal distribution study. However, the TB notification rate was relatively higher during spring, possibly due to the climate change and environmental variation [ 7 , 8 ]. The central and southern regions of Hainan Province exhibited higher TB notification rates, which are largely attributed to their higher population density, weak economic conditions, and limited access to medical resources [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%